Electrically controllable twisted-coiled artificial muscle actuators using surface-modified polyester fibers. (17th February 2017) - Park, Jungwoo; Yoo, Ji Wang; Seo, Hee Won; Lee, Youngkwan; Suhr, Jonghwan; Moon, Hyungpil; Koo, Ja Choon; Choi, Hyouk Ryeol; Hunt, Robert; Kim, Kwang Jin; Kim, Soo Hyun; Nam, Jae-Do
Abstract: As a new class of thermally activated actuators based on polymeric fibers, we investigated polyethylene terephthalate (PET) yarns for the development of a twisted-coiled polymer fiber actuator (TCA). The PET yarn TCA exhibited the maximum linear actuation up to 8.9% by external heating at above the glass transition temperature, 160 °C–180 °C. The payload of the actuator was successfully correlated with the preload and training-load conditions by an empirical equation. Furthermore, the PET-based TCA was electrically driven by Joule heating after the PET surface was metallization with silver. For the fast and precise control of PET yarn TCA, electroless silver plating was conducted to form electrical conductive layers on the PET fiber surface. The silver plated PET-based TCA was tested by Joule heating and the tensile actuation was increased up to 12.1% (6 V) due to the enhanced surface hardness and slippage of PET fibers. Overall, silver plating of the polymeric yarn provided a fast actuation speed and enhanced actuation performance of the TCA actuator by Joule heating, providing a great potential for being used in artificial muscle for biomimetic machines including robots, industrial actuators and powered exoskeletons.